Adult attention-deficit/hyperactivity disorder and bipolar disorder: diagnostic and management challenges - M. Barbosa; R. Guedes (European Psychiatry, 2022)
Introduction Attention-deficit/hyperactivity disorder (ADHD) and bipolar disorder (BD) are neurodevelopmental disorders that commonly persist into adulthood. ADHD in adults can resemble, and often co-occurs with, bipolar disorder (BD), which might lead to diagnostic errors, ineffective treatment and potentially serious adverse consequences.